Techno-Economic Optimization of Diesel–PV Hybrid Systems for Isolated Island Grids: Case Study of Tomia Island, Indonesia - Romi Adi Sanjaya Sebayang; Wawan Aries Widodo (Universitas Panca Marga, 2026)
Tomia Island, an isolated power system in Wakatobi Regency, Indonesia, relies primarily on diesel power generation, resulting in high operating costs, fuel dependency, and greenhouse gas emissions. Although the island has abundant solar energy resources, determining an appropriate photovoltaic (PV) capacity that balances technical performance, economic feasibility, and land availability remains a key challenge. This study aims to identify the optimal hybrid PV–diesel configuration to support a reliable and sustainable electricity supply. The analysis combined solar resource assessment, land suitability evaluation, and energy system modeling using the Low Emissions Analysis Platform (LEAP). Several development scenarios were compared to identify the most suitable system configuration based on technical and economic performance. The results indicate that a 2.5 MWp PV system integrated with a 4 MWh Battery Energy Storage System (BESS) provides the best balance between renewable energy utilization, system reliability, and investment cost. Compared with larger PV capacities, this configuration delivers substantial reductions in diesel fuel consumption and carbon emissions while avoiding unnecessary increases in investment and excess energy production. In addition, the integration of BESS improves supply reliability by storing surplus solar energy and supplying electricity during periods of low solar generation. Economic evaluation confirms that the proposed hybrid system is financially feasible, offering a competitive cost of electricity and a relatively short investment payback period. These findings demonstrate that the proposed PV–BESS–diesel configuration provides a practical and cost-effective pathway for reducing diesel dependence and accelerating the energy transition in isolated island power systems